2008
DOI: 10.1364/josaa.25.002263
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal chromatic aberration of the human infant eye

Abstract: Although the longitudinal chromatic aberration (LCA) of the adult eye has been studied, there are no data collected from the human infant eye. A chromatic retinoscope was used to measure cyclopleged infant and adult refractions with four pseudomonochromatic sources (centered at 472, 538, 589, and 652 nm) and with polychromatic light. The LCA of the infant eyes between 472 and 652 nm was a factor of 1.7 greater than the LCA found in the adult group: infant mean=1.62 D, SD ±0.14 D; adult mean=0.96 D, SD±0.17 D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 60 publications
1
9
0
1
Order By: Relevance
“…Uncompensated residual LCA, which would shift the refraction toward more hyperopic values, could have been compensated partially by the myopic shift due to the deeper retinal reflection in IR. This is consistent with a study in human infant eyes, about 2/3 the size of adult eyes, that reported that the chromatic difference of focus was not significantly higher in human infants with respect to that in adults (Wang, Candy, Teel & Jacobs, 2008). The opposing relative contributions of these two factors, longitudinal chromatic aberration and the difference in reflection layer in visible vs. IR light, may have resulted in the good agreement between retinoscopic and COAS refractions in the marmoset eye.…”
Section: Discussionsupporting
confidence: 93%
“…Uncompensated residual LCA, which would shift the refraction toward more hyperopic values, could have been compensated partially by the myopic shift due to the deeper retinal reflection in IR. This is consistent with a study in human infant eyes, about 2/3 the size of adult eyes, that reported that the chromatic difference of focus was not significantly higher in human infants with respect to that in adults (Wang, Candy, Teel & Jacobs, 2008). The opposing relative contributions of these two factors, longitudinal chromatic aberration and the difference in reflection layer in visible vs. IR light, may have resulted in the good agreement between retinoscopic and COAS refractions in the marmoset eye.…”
Section: Discussionsupporting
confidence: 93%
“…In the adult human eye, there is around 1.75 D of defocus due to LCA between 440 nm and 680 nm [ Figure ]; in the smaller, infant human eye there is approximately 1.7 times more LCA than in the adult eye because of the greater optical power of the infant eye (the ratio of LCA and optical power should be constant).…”
Section: Introductionmentioning
confidence: 99%
“…The major landmarks, the vascular system and optic nerve head, are easily visible with only a correction for defocus. This qualitative impression has been confirmed by careful study of the transmission properties28 and aberrations (both higher-order monochromatic29 and chromatic30) of the young eye (see also31). The data suggest that these combined aberrations are within a factor of two of those of an adult within weeks after birth, as illustrated in Figure 1, and are close to predictions based on relatively simple optical models of infant and adult eyes29, 32.…”
Section: Quantifying Visual Experience Using Retinal Image Qualitymentioning
confidence: 70%
“…Retinal images of point light sources (PSFs) simulating the combined effects of diffraction from the pupil, longitudinal chromatic aberration30 and higher order monochromatic aberrations (3 rd to 6 th order Zernike polynomials)29. The effect of longitudinal chromatic aberration was calculated every 10 nm, for wavelengths from 400 to 700nm, including the effect of V λ and assuming 555 nm is in focus on the retina.…”
Section: Figuresmentioning
confidence: 99%